Long term development in the pole vault: From performance analysis to training strategy - Czingon, H. (3rd European Pole Vault Conference - Köln 2008, 2008)
Herbert Czingon gave an overview of different sources of analytical data on the actual state of the athlete during his career. From easy video analysis, for which there are quite a lot of computer based solutions available today, to more complex biomechanical analysis in cooperation with scientific partners, there are many tools to analyze the state of the athlete. Also, testing different aspects of the preparation state of the athlete (speed, strength, special strength etc.) helps to understand the athletes' structure of performance. These tools can be used in a "top-down" way to generate insight from the most specific technical items and their biomechanical evidence to general physical aspects of the athlete's fitness. Using a "bottom-up" style planning method, coaches can develop individual strategies to generate a lastingly long-term concept for the athlete's development.